Immune Dysregulation and Cytokine Signatures in Adult Males with Epstein–Barr Virus Infection in Kirkuk City - Mohammed, Asmaa Jamal (Journal of Discoveries in Applied and Natural Science, 2026)
Introduction & Aim: Epstein–Barr virus (EBV) is an omnipresent herpesvirus, which infects the vast majority of humans and induces lifelong latency in B lymphocytes and has been associated with different autoimmune diseases as well as malignancies. Investigating on immunodysregulation, cytokine profile and T-cell activation in EBV-infected adult males. Materials and Methods: A cross-sectional study was carried out in Azadi Teaching Hospital, Kirkuk, Iraq during the period of April to November 2025. A total of 136 EBV-infected cases and 80 healthy controls were enrolled. EBV infection was determined by qualitative EBNA ELISA. Serum cytokines (IL‑6, TNF‑α, IFN‑γ, IL‑1β, IL‑10 and TGF-β) and soluble T cell markers (sCD4 and sCD8) were detected by ELISA. Results: Among 136 symptomatic participants, 82 (60.3%) were EBNA-positive. Clinical features included fever 58/82 (70.7%), cervical lymphadenopathy 61/82 (74.4%), and fatigue 54/82 (65.9%). EBNA-positive participants showed significantly elevated pro-inflammatory cytokines: IL‑6 48.3±12.5 pg/mL, TNF‑α 52.5±13.2 pg/mL, IFN‑γ 45.7±11.8 pg/mL, IL‑1β 38.7±10.3 pg/mL (controls: 15.4±5.9, 17.3±6.3, 14.7±5.1, 12.9±4.4, all p<0.001). Anti-inflammatory cytokines: IL‑10 22.4±6.7 pg/mL, TGF‑β 35.6±8.9 pg/mL (controls: 10.5±3.3, 19.1±5.6, p<0.001). Soluble T-cell markers: sCD4 7.8±1.9 ng/mL, sCD8 8.5±2.1 ng/mL (controls: 3.2±1.2, 3.5±1.3, p<0.001). ROC analysis indicated IL‑6, TNF‑α, and IFN‑γ had highest AUCs (0.94–0.96) for differentiating EBNA-positive from controls.